ANALGESIC POTENTIAL OF ETHANOL EXTRACT OF KETAPANG LEAVES (Terminalia catappa L.) ON MICE USING THE HOTPLATE METHOD - Rosa Juwita Hesturini; Ade Giriayu Anjani; Briandini Dwi Astuti; Afdyta Doria Bilhis (JURNAL PHARMA BHAKTA, 2025)
Background: Pain is a sensory experience from tissue damage that can occur over a certain duration. Pain management is generally carried out by administering analgesic drugs. Ketapang leaves have potential as a natural analgesic alternative. Objective: To evaluate the analgesic activity of ketapang leaf extract in male white mice. Methods: A total of 15 mice were divided into five groups: 0.5% Na CMC as a negative group, a positive control Asetil salisilat acid 500 mg/KgBW, and three treatment groups given sampel at doses of 300 mg/KgBW, 400 mg/KgBW, and 500 mg/KgBW. The analgesic test was conducted using the hot plate methog, and the mice's response to heat stimulus was observed for 60 minutes after oral suspension administration. Results: Extract at various doses significantly increased the latency period of the mice compared to the negative control group. The highest latency period was shown by the 500 mg/KgBW dose, which was 9.39 seconds. This suspected activity is due to the content of flavonoid, alkaloid, saponin, and steroid compounds, which may blockade of the cyclooxygenase pathway. Conclusion: The extract of ketapang leaves possesses analgesic percentages of 33%, 36%, and 55%, respectively. The most effective dose was 500 mg/KgBW, with an analgesic percentage of 55%.